One virus, many lives: a qualitative study of lived experiences and quality of life of adults from diverse backgrounds living in the UK during the COVID-19 pandemic. Issue 3 (1st March 2023) - Gogoi, Mayuri; Chaloner, Jonathan; Qureshi, Irtiza; Wobi, Fatimah; Al-Oraibi, Amani; Wilson, Heather; Suleman, Mehrunisha; Nellums, Laura; Pareek, Manish
Abstract : Objectives: The coronavirus disease 2019 (COVID-2019) pandemic has had far-reaching consequences for people's lives. In the UK, more than 23 million have been infected and nearly 185 000 have lost their lives. Previous research has looked at differential outcomes of COVID-19, based on socio-demographic factors such as age, sex, ethnicity and deprivation. We conducted a qualitative study with a diverse sample of adults living in the UK, to understand their lived experiences and quality of life (QoL) during the pandemic. Methods: Participants were recruited with the help of civil society partners and community organisations. Semi-structured interviews were conducted between May and July 2021. Interviews were recorded with permission and transcribed. Transcripts were analysed following an inductive analytical approach as outlined in the Framework Method. Results: 18 participants (≥16 years) representing different ethnicities, sexes, migration and employment statuses and educational qualifications took part. Five key themes and 14 subthemes were identified and presented using the QoL framework. The five key themes describe how COVID-19 affected the following aspects of QoL: (1) financial and economic, (2) physical health, (3) social, (4) mental health and (5) personal fulfilment and affective well-being. The narratives illustrated inequities in the impact of COVID-19 for individuals with intersecting social, economic, and health disparities. Conclusion: Our findings demonstrate the multidimensional and differential impact of the pandemic on different population groups, with most of the negative economic impacts being borne by people in low-paid and insecure jobs. Similarly, adverse social, physical and mental health impacts particularly affected people already experiencing displacement, violence, physical and mental illnesses or even those living alone. These findings indicate that COVID-19 impacts have been influenced by intersecting health and socioeconomic inequalities, which pre-existed. These inequities should be taken into consideration while designing pandemic recovery and rebuilding packages.